Total Quality Management and Organizational Performance in Manufacturing Companies: A Case of Mt. Elgon Millers - Jennifer Nyadoi (Uganda Christian University, 2024)
The study aimed to investigate the relationship between total quality management (TQM) practices and organizational performance at Mt. Elgon Millers Ltd. Adopting a case study design, the research employed both quantitative and qualitative approaches, involving a sample size of 60 participants. Specific objectives focused on examining storage management practices, materials handling practices, and lead time management practices in relation to organizational performance. The findings revealed significant correlations between TQM practices and organizational performance indicators. Specifically, effective storage management, efficient materials handling, and streamlined lead time management were found to positively influence organizational performance. In conclusion, the study recommends that Mt. Elgon Millers Ltd. prioritize the implementation of robust TQM practices to enhance overall organizational performance and competitiveness in the industry.